Physiological Responses to Rifle Carriage During Roller-Skiing in Elite Biathletes - Jonsson Kårström, Malin; McGawley, Kerry; Laaksonen, Marko S. (Frontiers in Physiology, 2019)
Purpose This study aimed to investigate the physiological factors affected by rifle carriage during biathlon skiing performance, as well as the sex differences associated with rifle carriage. Methods Seventeen national- and international-level biathletes (9 females and 8 males; age 23.0±3.3 years, V ̇O2max 59.4±7.6 mLkg-1min-1) performed a submaximal incremental test and a maximal time-trial (TT) using treadmill roller-skiing (gear 3, skating technique) on two occasions separated by at least 48 hours. One condition involved carrying the rifle on the back (WR) and the other condition no rifle (NR) and the tests were randomized. Submaximal V ̇O2, skiing speed at 4 mmolL-1 of blood lactate (speed@4mmol), gross efficiency (GE), aerobic (MRae) and anaerobic (MRan) metabolic rates, and V ̇O2max were determined. Results Submaximal V ̇O2 (at all intensities) and GE (16.7±0.9 vs 16.5±1.1%) were higher for WR compared to NR (p<0.05), while speed@4mmol was lower (3.1±0.4 vs 3.3±0.5 ms-1, p=0.040). TT performance was improved (4.6±0.4 vs 4.3±0.4 ms-1, p<0.001) and MRan was higher (31.3±8.0 vs 27.5±6.5 kJmin-1, p<0.01) for NR compared to WR, with no difference in V ̇O2max or MRae. For skiing WR, TT performance was correlated to speed@4mmol (r=0.81, p<0.001), MRan (r=0.65, p<0.01), V ̇O2max (r=0.51, p<0.05) and relative muscle (r=0.67, p<0.01) and fat (r=-0.67, p<0.01) masses. Speed@4mmol together with MRan explained more than 80% of the variation in TT performance (WR 84%, NR 81%). Despite a higher relative mass of the rifle in females compared with males (5.6±0.4 vs 5.0±0.4% of body mass, p=0.012), there were no sex differences associated with rifle carriage measured as absolute or relative differences. Conclusion Rifle carriage in biathlon skiing led to significantly higher physiological demands during submaximal exercise and reduced performance during maximal treadmill roller-skiing compared to NR for both sexes. The most important variables for performance in biathlon treadmill skiing seem to be speed@4mmol combined with MRan, both of which were lower for WR compared to NR. To improve skiing performance in biathlon, improving speed at 4 mmolL-1 of blood lactate and anaerobic energy delivery while carrying the rifle are recommended.